Study of Human Postural Control based on Electroencephalography Signals - Goh, Kwang Leng Alex (Curtin University, 2017)
Human movement requires adequate postural control. Stimulation of the sensory systems induces alterations in body sway. However, the role of cortical activity in maintaining balance remains unclear. The purpose of this research was to extend the understanding of cortical involvement in human postural control and provide direct and indirect cortical evidences from the visual system and postural demand. Ultimately, this research provides critical insight into the mechanisms of adaptive and maladaptive postural control.